Hepatitis B virus X protein inhibits p53 sequence-specific DNA binding, transcriptional activity, and association with transcription factor ERCC3. - Wang, X W (1994)
Chronic active hepatitis caused by infection with hepatitis B virus, a DNA virus, is a major risk factor for human hepatocellular carcinoma. Since the oncogenicity of several DNA viruses is dependent on the interaction of their viral oncoproteins with cellular tumor-suppressor gene products, we investigated the interaction between hepatitis B virus X protein (HBX) and human wild-type p53 protein. HBX complexes with the wild-type p53 protein and inhibits its sequence-specific DNA binding in vitro. HBX expression also inhibits p53-mediated transcriptional activation in vivo and the in vitro association of p53 and ERCC3, a general transcription factor involved in nucleotide excision repair. Therefore, HBX may affect a wide range of p53 functions and contribute to the molecular pathogenesis of human hepatocellular carcinoma.